Concurrent Biopsy During Liver-Directed Therapy: Considerations, Techniques, and Expanding Role in Clinical Practice - DePietro, Daniel M.; Kiefer, Ryan M.; Weinfurtner, Kelley; Hung, Matthew L. (Digestive Disease Interventions, 2026)
As oncologic care continues to evolve toward precision medicine, the role of percutaneous biopsy in the care of those with primary and metastatic liver cancers has expanded beyond diagnosis to include molecular and histologic profiling that guides treatment selection, prognostication, and predicts outcomes, amongst other uses. Interventional radiologists (IRs), who can perform both percutaneous liver biopsies and liver-directed therapies (LDT) to treat liver cancer, such as transarterial embolization and percutaneous ablation, are uniquely positioned to integrate concurrent biopsy into LDT procedural workflows. This review explores the rationale, safety, technical considerations, and clinical applications of performing liver tumor biopsy at the time of LDT. While data on concurrent biopsy safety during LDT are limited, early evidence suggests comparable complication rates to standalone procedures, with potential opportunities to detect and manage biopsy-related issues during the therapeutic intervention. Common cancers treated with LDT, such as hepatocellular carcinoma (HCC) and neuroendocrine tumors (NETs), provide clinical examples where concurrent biopsy during LDT provides valuable clinical information relevant to both IRs and other members of the treatment team. In HCC, biopsy enables histopathologic confirmation and molecular profiling (e.g., CTNNB1 and TP53 mutations, β-catenin and NRF2 pathway alterations), which correlate with LDT outcomes. In NETs, biopsy can detect changes in Ki-67 index and tumor grade that influence prognosis and treatment strategy. As performance of and evidence for biopsy at the time of LDT grows, IRs can drive the integration of concurrent biopsy into routine practice, optimizing personalized cancer care for their patients.
Keywords: percutaneous biopsy; liver-directed therapy; embolization; hepatocellular carcinoma; neuroendocrine tumor